Классические труды по методологии социологических исследований в представлениях студентов-социологов - Урсуленко, К.; Любивая, Т. (Социология: теория, методы, маркетинг, 2007)
The paper presents some results of empirical research concerning scientific heritage left by classic scholars in the sociological methodology. The research was conducted in the following way: Students of sociology departments from various universities expressed their opinions about works and scientific elaborations of sociological methodologists. For the inquiry, two of the most outstanding scientists from Ukraine (N.Pa nina, V.Paniotto), Russia (G.Batygin, V.Yadov), and USA (P.Lazarsfeld, S.Sud man) as representatives of classics in the sociological methodology had been selected. Furthermore, the acquaintance with scholars' works, their introduction to educational process, as well as evaluation of the classic scholars' contribution to development of sociology and appreciation of the significance of their ideas for students have been analyzed.